Diptera Collectionis P. Gabriel Strobl - IV (Exemplare-Nr. 1891-2334). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The fourth part of the evaluated material from Strobl’s collection of Diptera covers the specimens 1891-2334 (Acalyptrata only).